2009
DOI: 10.1177/0042098008098640
|View full text |Cite
|
Sign up to set email alerts
|

Mixing Housing Tenures: Is it Good for Social Well-being?

Abstract: Mixing tenures is now a widely accepted policy designed to tackle problems of social exclusion in disadvantaged neighbourhoods. However, the evidence base for mixing tenures is fragmented and ambiguous. With few exceptions, studies of mixed-tenure effects have been small, one-off investigations of individual communities, providing only a rudimentary basis for comparative evaluation. In attempting to address these issues, a national-level, ecological analysis of mixed tenure in Great Britain was conducted, usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
74
0
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 91 publications
(79 citation statements)
references
References 33 publications
2
74
0
3
Order By: Relevance
“…Several studies have compared outcomes for different geographical scales and found significant differences (See Buck, 2001;Bolster et al, 2007;Graham et al, 2009). We are aware that there is no one-to-one relationship between administrative areas and neighbourhoods as perceived by residents (see Galster, 2001), but it can be argued that smaller areas come closer to what people may perceive as their neighbourhood than larger areas.…”
Section: ---Table 1 About Here Please ---mentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have compared outcomes for different geographical scales and found significant differences (See Buck, 2001;Bolster et al, 2007;Graham et al, 2009). We are aware that there is no one-to-one relationship between administrative areas and neighbourhoods as perceived by residents (see Galster, 2001), but it can be argued that smaller areas come closer to what people may perceive as their neighbourhood than larger areas.…”
Section: ---Table 1 About Here Please ---mentioning
confidence: 99%
“…Previous work suggests that lower level geographies better represent neighbourhoods and there is evidence that neighbourhood effects are more pronounced when a lower geographical scale is used (see Buck, 2001;Bolster et al, 2007;Graham et al, 2009). To test the effect of a lower geographical scale, we reran Models 2 and 4 using neighbourhood characteristics on the Output Area level (see Table 4).…”
Section: Geographical Scale Of Neighbourhoodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies use large scale units to represent a neighbourhood (see for example Bolster, et al 2007), while others use multiple scales acknowledging that no one definition of neighbourhood is likely to be sufficient to capture all the potential interactions that could be included in the neighbourhood effects literature (see for instance, Buck 2001;Graham, et al 2009;van Ham and Manley 2010;Manley and van Ham 2012). An additional problem here is what Kwan (2012) termed the uncertain context problem: as well as uncertainty about where the neighbourhood boundaries should fall, there is also uncertainty relating to whether or not the chosen units reflect the spatial scale of the processes that they are being used to represent (see also Manley et al 2006 for a demonstration of this problem with British Census data).…”
Section: Methodsmentioning
confidence: 99%
“…However, while assimilationist tendencies in theory and policy prevail, we have also witnessed the emergence of a wave of counter-theories grounded in the belief that diversity is positive and must be embraced as a trait that can bolster social cohesion (among other things). The contributions of such works are especially notable in the area of social mixing -in terms of both theory and policy practice (see Graham et al 2009;Camina and Wood 2009;Joseph and Chaskin 2010). Social mixing policies identify and encourage greater mixing across income groups and between ethnic communities as a tool for establishing and strengthening social cohesion ).…”
Section: Introductionmentioning
confidence: 99%